Patterns of Gay Male and Lesbian Partnering in the Metropolitan Areas of the United States in 2010 - Poston, Dudley L.; Chang, Yu-Ting (Frontiers in Sociology, 2016)
In this paper we examine the degree of prevalence of partnered gay male households and partnered lesbian households in the metropolitan areas of the U.S. in 2010. We first discuss the same-sex partnering data from the 2010 U.S. Census, their biases and problems, and the adjustments researchers have developed to address the problems. We add a statistical adjustment to the data and then calculate for each of the 366 metropolitan areas of the U.S. prevalence ratios for gay male couples and for lesbian couples, and for comparative purposes, for opposite-sex cohabiting couples and opposite-sex married couples. Then we propose and test several ecological hypotheses to account for the variability among the metropolitan areas in the partnering ratios.